Hepatotoxicity of New Oral Anticoagulants - A. R. Kasimova; A. V. Philippova (Guryanova); A. S. Kolbin (Столичная издательская компания, 2018)
Aim. To summarize and systematize the information published in open sources on the development of various manifestations of liver damage in the use of the new oral anticoagulants (NOAC) for the registered indications and to analyze the published clinical cases of drug induced liver injury (DILI) development.Material and methods. Search queries for keywords were made in the PubMed (MEDLINE), Scopus, Elibrary and Kiberleninka databases. The search query was composed of the name of the medicinal product (international non-proprietary and commercial name) or the common name of the group and words describing the different variants of the liver damage.Results. As a result of the search 1497 articles were found. Duplicate articles, articles that do not match the review topic, and articles whose full-text version is not available were removed from the search results. Articles that do not describe specific clinical cases have also been excluded. The review includes 14 articles, published from 2007 to March 2018 in Russian and English and one article in French describing clinical cases of different types of hepatotoxicity in the application of NOAC.Conclusions. Published clinical cases suggest that NOAC cause undesirable phenomena such as hepatotoxicity, the mechanism and frequency of which remain unclear.